Strategic Thinking Model for Top Business Managers and Employees - Mojtaba Amiri, Farzad Azimi, Manouchehr Ansari (Opción, 2019)
In this paper, the strategic thinking model of top Iranian company managers and employees has been compared and presented to help the companies interested in entering Iran’s market operate independently or in partnership with these top companies. The study was conducted using a mixed-methods (qualitative and quantitative) approach. The influence of each factor was determined using the collected data. As a result, the majority of respondents believe in fundamental environmental changes and outside the focus of attention. As a conclusion, organizations need to enhance strategic thinking capability throughout the organization through education in order to achieve their organizational goals